Caring for people during mass casualty – the dengue case in Rio de Janeiro, Brazil - Isabel CF da Cruz (Online Brazilian Journal of Nursing, 2008)
Although the nurse’s role during a disaster, or a epidemy as dengue, may vary, the nursing care focuses on essential care from a perspective of what is best for all patients. Triage is pointed out as one of the tasks that the nurse can manage with success.